2013
DOI: 10.1590/s0034-8910.2013047004557
|View full text |Cite
|
Sign up to set email alerts
|

Transferencia de renda no Brasil e desfechos nutricionais: revisao sistematica

Abstract: OBJECTIVETo analyze the influence of conditional cash transfer programs on diet and nutrition outcomes among beneficiary families in Brazil.METHODSA systematic review of literature was carried out with original evaluation studies conducted in Brazil, including all types of clinical trials and observational studies. The search was conducted in PubMed, Scopus, Web of Science and LILACS databases for papers published since 1990. The studies were analyzed according to the program evaluated, participants, study des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
14

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 33 publications
0
21
0
14
Order By: Relevance
“…Regarding the factors related to household access to food, which directly affect the profile of children's food practices, conditional transfer programs such as the PBF can increase access to healthier foods for low-income individuals and contribute to improving conditions that today favor food and nutritional insecurity. A systematic review found a positive association between the participation of families in these programs in Brazil and the improvement of food and nutrition 49 . However, although PBF promotes food accessibility, it does not necessarily imply an improvement in the nutritional quality of food 50 , since greater purchasing power is not the only factor that favors healthy practices.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the factors related to household access to food, which directly affect the profile of children's food practices, conditional transfer programs such as the PBF can increase access to healthier foods for low-income individuals and contribute to improving conditions that today favor food and nutritional insecurity. A systematic review found a positive association between the participation of families in these programs in Brazil and the improvement of food and nutrition 49 . However, although PBF promotes food accessibility, it does not necessarily imply an improvement in the nutritional quality of food 50 , since greater purchasing power is not the only factor that favors healthy practices.…”
Section: Discussionmentioning
confidence: 99%
“…Ainda que estas regiões apresentem elevadas prevalências de IAG, houve uma redução expressiva nas prevalências entre 2004 e 2013 6 . Investimentos Federais no combate à pobreza extrema, como o programa Bolsa Família podem estar contribuindo para essa redução na IAG e maior acesso a alimentos 34 . Porém, independente destes esforços, é nítida a necessidade de homogeneizar essa ocorrência da IAG em percentuais mínimos, no país como um todo.…”
Section: Resultsunclassified
“…Programas sociais como o PBF, que fazem repasse de recursos para a população de mais baixa renda, contribuem com o cuidado em saúde e educação no combate à pobreza e a fome, uma vez que facilitam o acesso aos alimentos por parte das populações vulneráveis. 26 A avaliação da Escala Brasileira de Insegurança Alimentar revelou que dois entrevistados se encontravam em situação de segurança alimentar, quatro em insegurança alimentar leve, ligada a questões de acesso e qualidade dos alimentos e cinco em insegurança alimentar moderada, ou seja, a alimentação era comprometida quanto a sua quantidade. Para auxiliar no aumento ao acesso aos alimentos, quase metade dos catadores referiu fazer uso de hortas em seus domicílios.…”
Section: Resultsunclassified
“…Este contribui para a aquisição de bens necessários, como alimentos, e o acompanhamento da saúde e da educação das famílias que vivem em maior vulnerabilidade e necessitam dessas ações enquanto medida emergencial. 26 Com relação ao autocuidado, todas as catadoras afirmaram que precisam reservar para elas um tempo na rotina, mas a grande preocupação é não conseguir dar conta das atividades do dia a dia, como observado na fala: "A gente tem medo de que falte tempo para os outros, de arrumar a casa, de ajudar os outros ou até fazer o almoço de domingo, aí acabamos não tirando tempo para pensar na gente, mas acho que é importante, estamos tentando" (CATADORA 3). A dupla ou até tripla jornada de trabalho torna-se um importante fator para a condição de saúde, uma vez que essa sobrecarga faz com que as catadoras não consigam priorizar suas necessidades.…”
Section: Oficina 3 -Busca Da Efetivação De Direitos E a Importância Dunclassified